Comparación del espacio de la vía aérea faríngea en radiografías laterales de cabeza de individuos de clase I y II esquelética - Razo Huillca, Santiago (2022)
Objective: To compare the space of the pharyngeal airway (nasopharynx and oropharynx) through lateral X-ray analysis in skeletal class II individuals with a control group composed of skeletal class I individuals. Materials and methods: This study was of the observational, descriptive, transversal, and prospective type. The sample was made up by 60 lateral head radiographs distributed between 30 class I (ANB 2°±2° and class I malocclusion) and 30 skeletal class II radiographs (ANB>5° and malocclusion class II-1). Measurements of the airway space in the oropharynx and nasopharynx were taken in mm through the McNamara method on lateral head radiographs. Results: The average space found in the oropharynx in class I was 11.71mm ± 3.18mm. In the class II group, it was 10.73mm ± 2.36mm. No significant differences were found (p=0.18). The average space found in the nasopharynx in the class I group was 18.45mm ± 4.11mm. In the class II group, it was 19.10mm ± 3.89mm. There were no significant differences found (p=0.53). Conclusion: The airway space in mm. of the nasopharynx presents similar values in millimeters in subjects with Class I and Class II skeletal malocclusion. There is no difference in the airway spaces of the oropharynx in subjects with Class I and Class II Malocclusions.